Length sorting of single-walled carbon nanotubes using ultracentrifugation - Chia, Kin Wei. (2010)
The separation of Single-Walled Carbon Nanotubes (SWCNTs) and the sorting of its length via ultracentrifugation in high density medium, Iodixanol, is presented in this report. Significant quantities and data are extracted to analyse the dependency of the length of the nanotubes against the UV-Vis-IR spectroscopy and thus realizing that it has good optical properties for longer length. In addition, with the aid of the Atomic Force Microscopy (AFM) to measure the SWCNTs’ lengths, the report will attempt to establish a relationship between the measured lengths with the Intensity absorbance from the UV-Vis-IR spectroscopy. This is to relate to the problem of the time consuming method of having AFM to measure SWCNT lengths.